2013
DOI: 10.11118/actaun201260080229
|View full text |Cite
|
Sign up to set email alerts
|

Response of grapevine leaves to Plasmopara viticola infection by means of measurement of reflectance and fluorescence signals

Abstract: Response of grapevine leaf tissue naturally infected by Plasmopara viticola in field was measured by means of chlorophyll fluorescence and reflectance signals. Three susceptible grapevine varieties (Cabernet Sauvignon, Pinot Blanc and Pinot Gris) were used in this study. Since the infection impairs photosynthetic activity, distribution of FV/FM parameter (maximum quantum yield of Photosystem II) over the leaf was effective to discriminate healthy and naturally infected leaf tissue. FV/FM was reduced ~ 25% in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This allows us to determine the stage of leaf senescence, which according to the results of the present study correlates with berry ripeness (Figure 2). According to Sebela et al (2012) the chlorophyll content and CRI1 values increased with increased concentration of pigments. The CRI1 index measures carotenoids in leaves similarly to the CRI2 index (Gitelson, 2012).…”
Section: Correlação Para Tss Previsto Utilizando A) Mlr E B) Svm Em Cmentioning
confidence: 95%
See 1 more Smart Citation
“…This allows us to determine the stage of leaf senescence, which according to the results of the present study correlates with berry ripeness (Figure 2). According to Sebela et al (2012) the chlorophyll content and CRI1 values increased with increased concentration of pigments. The CRI1 index measures carotenoids in leaves similarly to the CRI2 index (Gitelson, 2012).…”
Section: Correlação Para Tss Previsto Utilizando A) Mlr E B) Svm Em Cmentioning
confidence: 95%
“…A previous study by Zartaloudis et al (2015) showed that the CRI2 index was more appropriate index compared to other carotenoid indices for tracking leaf carotenoid changes of olives due to Verticillium wilt infection. Work conducted by Sebela et al (2012) showed that the CRI1 index was the most suitable index for detecting the increase in the carotenoid content of grapevine leaves due to Plasmopara viticola infection. Moreover, Meggio et al (2010) showed that grape quality indicators are correlated with the CRI2 index.…”
Section: Introductionmentioning
confidence: 99%